Stress and poor quality of sleep: risk factors contributing to type 2 diabetes mellitus - Baharudin, Mohamad Sharul Fahmi; Soe, May Khin Soe; E. Zainudin, Engku Nuraishah Huda; Bahaludin, Hafizah; Abdul Rahim, Roslina; Andylim, Nizafaziasyida Fauzee; Mohd Mansor, Mohd Amin; Yaacob, Norhafiza (2019)
Background and Aims: Sleep can affect blood sugar levels, and blood glucose control can also affect person’s sleep. This can be considered as vicious cycle. Stress and lack of sleep have been shown to increase blood sugar levels and the risk of diabetes mellitus. This study conducted at Hospital Pekan and aimed to evaluate how perceived stress score (PSS) and quality of sleep are influent to Type 2 Diabetes Mellitus patients. In addition, this study determined to check the statistically significant difference between the T2DM patients and healthy group based on the biochemical parameters. Methods: A case-control comparative study was conducted to recognize the contribution of stress and sleep quality in total of 98 subjects. Among 98 subjects, 49 were healthy and the rest were T2DM patients. R studio was used for conducting the statistical analyses. First, descriptive analyses were performed to describe the data in general. Next, independent t-test was employed to find the significance of difference between healthy and T2DM patients based on the PSS, quality of sleep and biochemical parameters. Results: The mean of PSS for T2DM patient was 48.27 ±5.72 which was higher than healthy group’s mean value (28.92±4.03). Meanwhile, the mean of Pittsburgh Sleep Quality Index (PSQI) score was 7.24±2.35 in T2DM patients and 4.84±2.81 in normal healthy adults. The results found that the T2DM patients have high stress and less sleep quality as compared to the healthy group. In addition, the item scale showed adequate internal reliability with a Cronbach’s coefficient alpha of . Moreover, the biochemical parameters namely FBG, Triglyceride, HDL-c, LDL-c, HbA1c, and serum cortisol were observed a significant difference between the T2DM patients and healthy group. Conclusions: This study provides the strong evidence that T2DM patients have poorer psychological wellbeing contrasting with control group. Moreover, this Psycho-physiological study highlighted that stress and sleep disturbance in diabetes patient lead to poor glycaemic control and consequently deteriorate the biochemical changes in body. This noble finding suggests expending the investigation with larger sample size in Malaysia.